1983
DOI: 10.1507/endocrj1954.30.601
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of specific binding of epidermal growth factor (EGF) on human tumor cell lines.

Abstract: Using seventeen human tumor cell lines derived from a variety of tissues, specific binding sites for epidermal growth factor (EGF), a mouse submandibular glandderived growth factor, has been characterized.A significant amount of membranebound EGF receptors, although considerably varied, was demonstrated in all the tumor cell lines studied. Epidermoid carcinoma appeared to have more EGF receptors than adenocarcinoma.One small cell carcinoma of the lung, one choriocarcinoma of the stomach and three bone tumors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Binding experiments were performed as previously reported (Hirata, Uchihashi, Fujita, Matsukura, Motoyama, Kaku and Koshimizu 1983). In brief, the cells were replaced with 1 ml Hank's medium, pH 7.4, containing 0.1% bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…Binding experiments were performed as previously reported (Hirata, Uchihashi, Fujita, Matsukura, Motoyama, Kaku and Koshimizu 1983). In brief, the cells were replaced with 1 ml Hank's medium, pH 7.4, containing 0.1% bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…Binding studies were performed as previously reported (Hirata et al 1983). In brief, the confluent cells were replaced with 1 ml Hanks' medium, pH 7.4, containing 0.1% bovine serum albumin (binding medium).…”
Section: Bound(f Mol)mentioning
confidence: 99%
“…Numerous reports describe the interaction of EGF with intact cells in monolayers (1,5,11), but no studies have been reported using cells in matrices. Although most biological molecules can readily penetrate the collagen gels, diffusion coefficient are substantially reduced (10).…”
Section: Introductionmentioning
confidence: 99%